The Quantitave Case of Children Libraries in Turkey (1995-2000) - Candemir Demircan (Türk Kütüphaneciliği)
The purpose o f this study is to p u t forth the quantitative qualities of the Children's Libraries in Turkey between the years 1995-2000 in terms of various variables. These libraries were closed by being turned over to Public Libraries at the end of the year 2000. Collected data in this study has been classified and p u t into charts according to the research questions. The latest situation of the Children’s Libraries before they were turned over to Public Libraries will be discussed. Besides, this study will be beneficial fo r the researchers who study about children's literature, children's education and librarianship fields by showing the recent situation of the children's libraries.